Novel Method for Collecting Skin Microbiome Samples From Free‐Ranging Bottlenose Dolphin - Joseph J. Hansen; Jennifer C. G. Bloodgood; Brandi Kiel Reese; Thomas B. Waltzek; Kevin Barry; Thibaut Bouveroux; Carrie Sinclair; Kuttichantran Subramaniam; Keith D. Mullin; Ruth H. Carmichael (Marine Mammal Science, 2026)
Cetacean skin microbiome samples are traditionally collected by swabbing the skin of captured animals or using skin tissue from remote biopsies. The effects of different sampling methods are not well understood, and factors such as swab type and storage methods may affect the microbiome. The objective of this study was to determine if samples collected by swabbing biopsied skin from bottlenose dolphins yield sufficient microbial DNA for gene sequencing, while testing if commonly used sampling and storage methods affect the skin microbiome. Skin swab samples were collected during remote biopsy surveys with either a nylon flocked swab and flash frozen with liquid nitrogen or with a cotton swab and stored in RNAlater. Sequencing of the V3–V4 region of the 16S rRNA gene revealed swabs from dolphin skin biopsies yielded sufficient DNA to characterize the microbiome. We found no significant difference between the two sampling and storage methods tested, suggesting that studies using different techniques may be comparable. This work also demonstrates a novel technique to collect samples for interpretation of the skin microbiome of free‐ranging animals. Benefits of this method are that it can be done without capture and preserves valuable and typically scarce biopsy skin samples for other analyses.

Developmental programming: Sex-specific effects of prenatal exposure to a real-life mixture of environmental chemicals on liver function and transcriptome in sheep - Soundara Viveka Thangaraj; Michelle Bellingham; Richard Lea; Neil Evans; Kevin Sinclair; Vasantha Padmanabhan (Environmental Pollution, 2025)

In-utero exposure to real-life environmental chemicals disrupts gene expression within the hypothalamo-pituitary-gonadal axis of prepubertal and adult rams - Mohammad Ghasemzadeh Hasankolaei; Neil P. Evans; Chris S. Elcombe; Richard G. Lea; Kevin D. Sinclair; Vasantha Padmanabhan; Michelle Bellingham (Environmental Research, 2025)

Host response signature trends in persistent bacteraemia and metastatic infection due to Staphylococcus aureus and Gram-negative bacilli: a prospective multicentre observational study - Anna Maria Peri; Nastaran Rafiei; Kevin O’Callaghan; Anna Brischetto; Bianca Graves; Holly Sinclair; Matthew Eustace; Karen Lim; Jill Parkes-Smith; Adam Stewart; Natalie Davidson; Alexis Tabah; et al. (Infectious Diseases, 2024)

Sexually dimorphic impact of preconceptional and gestational exposure to a real-life environmental chemical mixture (biosolids) on offspring growth dynamics and puberty in sheep - Neil P. Evans; Michelle Bellingham; Christopher S. Elcombe; Mohammad Ghasemzadeh-Hasankolaei; Richard G. Lea; Kevin D. Sinclair; Vasantha Padmanabhan (Environmental Toxicology and Pharmacology, 2023)

Developmental exposure to a real-life environmental chemical mixture alters testicular transcription factor expression in neonatal and pre-pubertal rams, with morphological changes persisting into adulthood - Chris S. Elcombe; Ana Monteiro; Mohammad Ghasemzadeh-Hasankolaei; Vasantha Padmanabhan; Richard Lea; Kevin D. Sinclair; Neil P. Evans; Michelle Bellingham (Environmental Toxicology and Pharmacology, 2023)

Enhanced progesterone support during stimulated cycles of transvaginal follicular aspiration improves bovine in vitro embryo production - Rob Simmons; Des AR. Tutt; Gizem Guven-Ates; Wing Yee Kwong; R. Labrecque; Federico Randi; Kevin D. Sinclair (Theriogenology, 2023)

Water–fat MRI in a hibernator reveals seasonal growth of white and brown adipose tissue without cold exposure - Amanda MacCannell; Kevin Sinclair; Lannette Friesen-Waldner; Charles A. McKenzie; James F. Staples (Journal of Comparative Physiology B, 2017)